The effect of physiological and environmental conditions on smolt migration in Atlantic salmon Salmo salar. Issue 2 (1st October 2018) - Persson, Lo; Kagervall, Anders; Leonardsson, Kjell; Royan, Mansour; Alanärä, Anders
Abstract: Hydropower development has negatively influenced Atlantic salmon ( Salmo salar ) populations. Compensatory hatchery‐rearing programmes exist, but released fish suffer from high mortality that may be related to the lack of experience from natural environments in hatchery‐reared smolts and their large body size and high energetic state. Here, we used acoustic telemetry to test how body size, energetic state, and the environmental conditions of the river affect migration in hatchery‐reared smolts. The study was conducted in three consecutive years between 2011 and 2013 in the lower part of the River Umeälven, Sweden. For individual fish, there was no effect of body size but the energetic state of the fish had a negative effect on sea entry. The most important factor affecting sea entry rate was the water discharge in the old river bed that differed among years. Smolts were more likely to enter the sea in years when the discharge was high or when the discharge increased substantially shortly after release. Hatchery‐reared fish had higher migration speed at a slower flowing section compared with a faster flowing section, which was likely a result of large hesitation to enter the rapid section. The increase in water discharge led to an increase in fish migration speed disproportional to the increase in water velocity. Our results highlight the importance of water discharge for the smolts during smolt migration, and we argue that concern should be given to migrating fish when managing regulated rivers.